Comparison Of Financial Performance Of Sharia Bank Using A Value Added And Profit Loss Approach (Case Study In Pt. Bank Sulselbar Kc Syariah Makassar) - Nasrullah, Nasrullah; Sarda, Sultan; Amiruddin, Andi Noviantika (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study to analyze the financial performance of PT. Bank Sulselbar KC. Syariah Makassar using a value added and profit and loss approach based on the ratio of ROA, ROE and NPM. This research is a type of quantitative research with a comparative descriptive approach. The population of this study is the financial statements of PT. Bank Sulselbar KC. Makassar Sharia, while the sample used is the 2019-2020 financial statements for each approach, namely the value added and profit and loss approach. The results of this study indicate that the average ROA, ROE and NPM ratios differ significantly between the value added approach and the profit and loss approach. Likewise with the overall performance